Design and Implementation of a Smart Wireless Access Point for A Gas Station (SWAP-GS) - Odinakachukwu, Duru Levi; Chukwueloka, Okorie Amarachukwu; Uwah, Onwuka Nelly; Monday, Idio Nelly; Victor, Njoku Abiaziem; Agbor, Ofuka Hope; Chizurumoke, Okafor David; Effiong, Essien Mfon-Abasi (Darul Yasin Al Sys, 2024)
The gas distribution sector is a good fit for wireless communications, especially considering how often distribution facilities are located in distant areas. The underlying communications infrastructure needs to be extremely dependable, with a resilient system that links sensors and controls throughout a vast field area network, when working with accumulated and real-time data. The resulting detail assists managers in creating and modifying business processes, managing the station site fully, and increasing operational efficiency. A wireless gas station offers an architecture based on Wi-Fi standards for applications that track and collect data all the way down sto the sensor level. The goal of the research was to install a wireless infrastructure network at a service station. When used in a gas station, plant, enable users to access real-time information, exchange and share sensor readings from the access point, and develop a smart wireless access point system with higher secure encryption than the generic wireless network. The NodeMCU microcontroller, which broadcasts the real-time data to the clients, receives inputs from a temperature, pressure, and humidity sensor. This allows the system to do such activities. It was believed that the built wireless infrastructure will enhance the existing LAN infrastructures. A few basic prerequisites are taken into account. First and foremost, a microcontroller, a sensor unit, software design, and compliance with IEEE 802.11 standards were required.